2022
DOI: 10.1021/acs.inorgchem.1c02956
|View full text |Cite
|
Sign up to set email alerts
|

Ir(IV) Sulfoxide-Pincer Complexes by Three-Electron Oxidative Additions of Br2 and I2. Unprecedented Trap-Free Reductive Elimination of I2 from a formal d5 Metal

Abstract: Oxidative addition of 1.5 equiv of bromine or iodine to a Ir(I) sulfoxide pincer complex affords the corresponding Ir(IV) tris-bromido or tris-iodido complexes, respectively. The unprecedented trap-free reductive elimination of iodine from the Ir(IV)-iodido complex is induced by coordination of ligands or donor solvents. In the case of added I − , the isostructural tris-iodo Ir(III)-ate complex is quickly generated, which then can be readily reoxidized to the Ir(IV)-iodido complex with FcPF 6 or electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 103 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…2.2 μ B is higher than the spin-only value for 1 unpaired electron. The EPR spectrum in CH 2 Cl 2 at 4 K (Figure ) showed a rhombic signal with stimulated g values g x = 2.06, g y = 1.91, and g z = 2.84, which compare well with those for reported Ir­(IV) complexes. The hyperfine coupling constants for Ir­(IV) ( I = 3/2) were determined to be A xx = 60, A yy = 40, and A zz = 18 G. The EPR data indicated that 6·OTf is an Ir­(IV) complex instead of an Ir­(III) complex with an organic radical. Unfortunately, despite many attempts, we have not been able to obtain X-ray quality crystals of 6·OTf for structure determination.…”
Section: Resultssupporting
confidence: 55%
“…2.2 μ B is higher than the spin-only value for 1 unpaired electron. The EPR spectrum in CH 2 Cl 2 at 4 K (Figure ) showed a rhombic signal with stimulated g values g x = 2.06, g y = 1.91, and g z = 2.84, which compare well with those for reported Ir­(IV) complexes. The hyperfine coupling constants for Ir­(IV) ( I = 3/2) were determined to be A xx = 60, A yy = 40, and A zz = 18 G. The EPR data indicated that 6·OTf is an Ir­(IV) complex instead of an Ir­(III) complex with an organic radical. Unfortunately, despite many attempts, we have not been able to obtain X-ray quality crystals of 6·OTf for structure determination.…”
Section: Resultssupporting
confidence: 55%
“…The difference spectrum between those of the reaction mixture and the [FeCp* 2 ]OTf provided signals rhombic in g‐value ( g xx =2.091, g yy =1.920, and g zz = 1.817, Figure 4A). The relatively small g anisotropy values suggested delocalization of the unpaired electron over the Ir center and the ligand [12–13] . This was confirmed by calculated spin‐density plot of 2 , which showed the radical is mostly metal‐based, with non‐negligible delocalization at one dpa‐NHC moiety (Figure 4B and Table S2).…”
Section: Resultsmentioning
confidence: 54%
“…Most of these were synthesized from oxidative addition of a polar element-hydrogen (EÀ H) bond. Another general strategy to access high valent iridium complexes is by electrochemical/chemical oxidation methods using X-type πdonating ligands, usually involving electronegative elements of Group 15-17 (S, [12] O, [13] N, [14] halides or a combination of these) [15] carrying lone pairs of electrons (Figure 1). Through the metal-ligand secondary π interactions, the usually low-lying filled 5d orbitals are destabilized (a phenomenon known as anisotropic field oxidation enhancement, AFOE), [15h] which allows further oxidization.…”
Section: Introductionmentioning
confidence: 99%
“…4 Originally commercialized as the (R,S)-racemate, the key ingredients for the successful "chiral switch" to (S)-metolachlor were the "magic mixture" of the (R)-(S) ferrocenyl diphosphine ligand "Xyliphos" of the Josiphos class, a cocatalytic Brønsted acid (CH 3 COOH or H 2 SO 4 ), and cocatalytic amounts of an iodide salt such as [ n Bu 4 N]I. 5 Note that only the combination of an acid and iodide leads to the increase in reactivity as well as enantioselectivity, while this is not the case if only one of these two components is added. 6 The beneficial effect of iodide is reminiscent of the Monsanto and Cativa processes, 7 which are text-book examples for group 9 element transition-metal catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nowadays, it represents the largest-scale enantioselective chemical process producing 10,000 t/a of the herbicide (1 S )-metolachlor with an optical purity of approximately 80% ee . Originally commercialized as the ( R,S )-racemate, the key ingredients for the successful “chiral switch” to ( S )-metolachlor were the “magic mixture” of the ( R )-( S ) ferrocenyl diphosphine ligand “Xyliphos” of the Josiphos class, a co-catalytic Brønsted acid (CH 3 COOH or H 2 SO 4 ), and co-catalytic amounts of an iodide salt such as [ n Bu 4 N]­I . Note that only the combination of an acid and iodide leads to the increase in reactivity as well as enantioselectivity, while this is not the case if only one of these two components is added .…”
Section: Introductionmentioning
confidence: 99%